environmental education projects and their contribution in the peruvian reality - Gómez Gallardo, Luz Marina (2014)
This article aims to raise awareness of the contribution of Environmental Education Projects Basic Education and Higher Education in the Peruvian reality full of contrasts and changes, framed within a globalized world. Environmental problems have worsened in recent years throughout the world, this situation has determined that environmental education should be seriously considered. It is of interest in environmental education work time in formal, organized and projected into the future from schools and universities, that is, in the classroom (through projects) and in daily practice. In doing so we will be guided by the idea that environmental education is not a branch of science or a subject of separate study, but should be carried out in accordance with the principle of comprehensive education permanent.